Dietary Interventions and Physical Activity as Crucial Factors in the Prevention and Treatment of Metabolic Dysfunction-Associated Steatotic Liver Disease - Paweł Rajewski; Jakub Cieściński; Piotr Rajewski; Szymon Suwała; Alicja Rajewska; Maciej Potasz (Biomedicines)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most common chronic liver disease worldwide and affects nearly 30% of the adult population and 10% of the pediatric population. It is estimated that this number will double by 2030. MASLD is one of the leading causes of hepatocellular carcinoma, cirrhosis, and liver transplantation, as well as a significant risk factor for cardiovascular disease and mortality. Due to the ever-increasing number of patients, the long-term asymptomatic course of the disease, serious complications, and lack of preventive programs, as well as insufficient awareness of the disease among patients and doctors themselves, MASLD is a growing interdisciplinary problem and a real challenge for modern medicine. The main cause of MASLD is an inappropriate lifestyle—inadequate nutrition and insufficient physical activity, which lead to various components of metabolic syndrome. Lifestyle changes—appropriate diet, weight reduction, and systematic physical activity—are also the basis for the prevention and treatment of MASLD. Hence, in recent years, so much importance has been attached to lifestyle medicine, to non-pharmacological treatment as prevention of lifestyle diseases. The narrative review presents possible therapeutic options for non-pharmacological management in the prevention and treatment of MASLD. The best documented and available diets used in MASLD were discussed, focusing on the benefits and drawbacks of the Mediterranean, high-protein, ketogenic, and intermittent fasting diets. In addition, the most recent recommendations regarding physical activity are summarized.